Materials testing laboratory of the Public Works ministry of Buenos Aires Province, national pioneer in the Management of Science and Technology - Delgado, Arnoldo Oscar (2014)
First of its kind in Argentina, promptly recognized all over the LatinoAmerican sphere, the Materials Testing Laboratory of the Ministry of Public Works of Buenos Aires Province (LEMOP) was opened in 1942 under the motto Science and Research at the service of Technique and Industry, commitment that it tried to deepen two years later being reformulated as Materials Testing Laboratory and Technological Research (LEMIT), when the Second World War imposed to the national productive sector a new scenario for its consolidation. Having reached the zenith of its development under Coronel Mercante’s government (1946-1952), since 1955 it faced numerous difficulties that would end in its dissolution and reformulation by the military dictatorship in 1979, being its constituent parts incorporated to the Commission of Scientific Research of Buenos Aires Province. The purpose of his work is to describe some aspects of this special institution, whose mission and organizational scheme emulated successful models in the United States of America and Brazil, providing absolutely innovative characteristics for the Argentinean environment, either by its efforts for contacting the productive world, the management of economic-financial resources or the choice/training of its staff, all this looking towards the professionalization of the pure and applied research.